The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1121/1.4893333
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a two-interval, two-alternative infant behavioral testing procedure

Abstract: The purpose of this study was to evaluate the feasibility and efficiency of an observer-based, two-interval forced-choice infant psychophysical testing procedure. Ten of 11 infants (7–9 months of age) achieved a criterion of 80%-correct detection of a 50-dB sound pressure level noise band in a single testing session. Fewer trials were needed to reach criterion using the two-interval procedure than previously reported for the single-interval observer-based psychophysical procedure [Olsho, Koch, Halpin, and Cart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…While the current study used an adaptive procedure to estimate threshold, the same procedures could be used to evaluate percent correct performance at a fixed signal and/or masker level. Another possible modification is that the stimuli can be presented through other transducers, including the soundfield 13 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the current study used an adaptive procedure to estimate threshold, the same procedures could be used to evaluate percent correct performance at a fixed signal and/or masker level. Another possible modification is that the stimuli can be presented through other transducers, including the soundfield 13 22 .…”
Section: Discussionmentioning
confidence: 99%
“…After each trial, the observer selects the interval containing the signal based on the infant's behavior. The results reported by Browning et al 13 demonstrated that this procedure is both feasible and efficient for use with 7 to 9 month-old infants. The method for testing toddlers and preschoolers closely follows procedures for testing infants, with the caveat that children's responses to sound are shaped using methods common with CPA.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Researchers of hearing in infants should consider working together to develop a set of uniform stimuli that have been acoustically and psychoacoustically well characterized that would be suitable for use in infant studies. For many years, developmental psychoacoustics has focused on designing rigorous procedures for assessing performance in infants and children in a way that allows for comparison to adult performance (e.g., Aslin, Pisoni, Hennessy, & Perey, 1981;Browning, Buss, & Leibold, 2014;Schneider & Trehub, 1992;Trehub, Schneider, Thorpe, & Judge, 1991;Werker & Lalonde, 1988;Werner, 1995). As the interest in understanding infants' auditory processing in complex sound environments increases, it is imperative that we apply the same effort to the characterization of the sounds we use.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2IFC observer-based procedure, a signal is presented on each trial in one of two temporal intervals; the observer must decide which interval contained the signal. Browning, Buss, and Leibold (2014) evaluated the feasibility and efficiency of a 2IFC observer-based procedure using a 500-ms low-pass filtered broadband noise for 7-to 9-month-old infants with normal hearing. The signal was presented in one of two 500-ms temporal intervals, visually marked in real time, separated with a 300-ms interstimulus interval (ISI).…”
mentioning
confidence: 99%